Physical inactivity before stroke is associated with dependency in basic activities of daily living 3 months after stroke - Susts, Jevgenijs; Reinholdsson, Malin; Sunnerhagen, Katharina Stibrant; Abzhandadze, Tamar (Frontiers in Neurology, 2023)
Background: Physical inactivity is a leading risk factor for noncommunicable diseases, including stroke. Moreover, physical inactivity before stroke is associated with stroke severity, which, in turn, can cause disability. However, it remains unclear whether physical inactivity before stroke is associated with dependency in basic activities of daily living (ADL). Aim: To evaluate whether physical inactivity before stroke influences ADL dependence 3 months after stroke. Methods: This longitudinal study was based on data from three Swedish registries. Patients with acute stroke who were admitted to Sahlgrenska University Hospital between the November 9, 2014, and June 30, 2019, were included. Baseline data were collected from the three stroke units, and self-reported questionnaires were used to collect 3-month follow-up data. Physical inactivity before stroke was the primary independent variable which was self-reported using the Saltin–Grimby Physical Activity Level Scale. ADL dependency was a composite measure of three tasks: mobility, dressing, and toilet use. Binary logistic regression was used to explain the association between physical inactivity before stroke and basic ADL 3 months after stroke. Results: Overall, 3472 patients were included in the study. The median age was 75 years, 49% were physically inactive before stroke, and 75% had a mild stroke. ADL dependency at follow-up was reported to be 32%. Physically inactive patients, compare with physically active patients, had 2.35 times higher odds for ADL dependency 3 months after stroke (odds ratio 2.35 [95% confidence interval (CI) 1.94–2.86]). The model correctly classified 84% of the patients (the area under the receiver operating characteristic curve was 0.84 [95% CI 0.82–0.85]). Conclusion: The findings of this study suggest that physical inactivity before stroke is associated with dependency in basic ADL 3 months after stroke. Additionally, older age, female sex, pre-stroke living conditions and need of help, previous stroke, and admission stroke severity are significant contributors to dependency. The findings of this study suggest that patients who are physically inactive before stroke are more likely to be dependent in basic ADL after stroke.